Evaluación del nivel de sostenibilidad de la ESPAM MFL como aporte a la gestión ambiental universitaria - Vera Ayala, Génesis Lisbeth (2024)
In recent years, every institution, including those whose character is educational, must adopt a series of measures to mitigate and reduce their impacts related with environmental issues. Therefore, the purpose of this paper was to evaluate the sustainability level of ESPAM MFL. Furthermore, this research was non-experimental, bibliographic, exploratory, and descriptive. According to the diagnostic results, the polytechnic community possesses theoretical knowledge on environmental and sustainability topics, as these are specifically addressed in the curricula of the programs and through training and events organized by the institution. However, regarding campus environmental management, the polytechnic community is uninformed, as there are no specific internal policies to support it, with only 5.4% aligning with the Sustainable Development Goals. Similarly, in the research area, only 13.73% of topics are related to sustainability. Finally, the institution neither possesses nor implements an environmental management plan for its activities and processes. Based on the results of the applied GESU methodology, a score of 22% was obtained, indicating a deficient level of sustainability. Therefore, it is imperative to develop a sustainability plan that contributes to university environmental management, strengthens the institution's capabilities, capitalizes on opportunities, and addresses the identified threats and weaknesses.